'Unlocking Us': Analyzing the US election and its aftermath. (June 2021) - Chace, Sarah
The American presidential election of 2020 ended in the early hours of Thursday 7 January 2021, when the US Congress counted and certified the ballots of the Electoral College in the aftermath of a violent, Trump-supporting mob breaching the US Capitol. The spectacle of this assault may be analyzed for years to come, yet it is immediately clear that it was the result of authoritarian impulses on the part of the defeated president. Critical Leadership Studies has concerned itself with the 'problematization' of leadership theory, often examining distributions of power both within society and within the discipline itself. This article takes its title from Brené Brown's podcast, 'Unlocking Us', torqueing it in an effort to understand these events and their causes as a group dynamic that manifested between Trump and his supporters. I also make the argument that the anxiety fomented and falsely contained by Trump has its deeper origins in what Kuhn labeled 'paradigm shifts'. To deconstruct the kind of leadership that took place in the run-up to and the aftermath of the 2020 election—darkly charismatic, authoritarian, and cultish—I employ three lenses of analysis: paradigm shifts as progenitors of crisis; 'basic assumption' patterns of work avoidance in groups; and 'holding environments' as the imposition of salutary boundaries that foster growth. In combination, these three lenses offer an interpretation of recent events in America that enhances the dialectical approach proposed by Critical Leadership Theory.